Isatuximab monotherapy in relapsed/refractory multiple myeloma: A Japanese, multicenter, phase 1/2, safety and efficacy study. Issue 12 (15th October 2020) - Sunami, Kazutaka; Suzuki, Kenshi; Ri, Masaki; Matsumoto, Morio; Shimazaki, Chihiro; Asaoku, Hideki; Shibayama, Hirohiko; Ishizawa, Kenichi; Takamatsu, Hiroyuki; Ikeda, Takashi; Maruyama, Dai; Kaneko, Hitomi; et al.
Abstract: Isatuximab, an anti‐CD38 monoclonal antibody, targets cells that strongly express CD38 including malignant plasma cells. This open‐label, single‐arm, multicenter, phase 1/2 trial investigated the tolerability/safety and efficacy of isatuximab monotherapy in Japanese patients with heavily pretreated, relapsed/refractory multiple myeloma (RRMM). In Phase 1, patients were sequentially assigned to receive isatuximab once weekly (QW) in cycle 1 (4 weeks) and every 2 weeks (Q2W) in subsequent cycles. Cohort 1 (n = 3) received 10 mg/kg QW/Q2W; cohort 2 (n = 5) received 20 mg/kg QW/Q2W. No dose‐limiting toxicities occurred; the recommended dose for the single‐arm phase 2 study (n = 28) was 20 mg/kg QW/Q2W. The overall safety profile was consistent with the current knowledge of isatuximab. The most common adverse events were infusion reactions (42.9%; 12/28); all were grade 1/2 and generally occurred during the first infusion. The overall response rate with 20 mg/kg QW/Q2W isatuximab was 36.4% (12/33); patients with high‐risk cytogenetic abnormalities had comparable results. In phase 2, the median progression‐free survival was 4.7 (95% confidence interval, 3.75 to not reached) months. Median overall survival was not reached. Isatuximab monotherapy was well tolerated and effective in patients with heavily pretreated RRMM including high‐risk cytogenetic patients. This trial is registered at ClinicalTrials.gov as NCT02812706. Abstract : This open‐label, single‐arm, multicenter phase 1/2 trial investigated the tolerability/safety and efficacy of isatuximab monotherapy in Japanese patients with heavily pretreated, relapsed/refractory multiple myeloma (RRMM). The results demonstrated that isatuximab monotherapy was well tolerated and effective in patients with heavily pretreated RRMM, including high‐risk cytogenetic patients.